Simulacije dihanja - Dolenšek, Janez (Medicinski razgledi, 2008)
In addition to animal experiments, digital and analogue simulations are also used in medical research as well in medical education. In this way, various physiological systems can be studied and, if suitably presented, simulations can greatly improve the understanding of underlying processes. In initial simulations of pulmonary ventilation, mechanical models were used. Recently, these have been replaced by computer-assisted digital approaches. Our method involved the construction of a model of the lung and pulmonary ventilation. Analogue electronic elements (resistor, capacitors, amplifiers, etc.) were used. The constructed circuit was analyzed by applying Electronics Workbench software. In this way, normal quiet breathing in humans at rest and bronchoconstriction in the lung was simulated. Under the first conditions, thetidal volume and pleural pressure were 500 ml and -5 to -7.5 cm flzO, respectively. The maximal negative/positive alveolar pressure was -1/+1 cm H2O. Bronchoconstriction resulted in a prolonged expiration, a decrease of thetidal volume, about a 50% decrease in alveolar ventilation and a moderate increase in the functional residual capacity. The compensation, i. e. to bringventilation back to normal, was achieved by manual adjustments. The simulation results agree well with the published data. The performance of the circuit underlying our model is very stable and user-friendly. It can be used for research as well as for medical education. In the future, we intend to upgrade the circuitry by adding a negative feedback loop to achieve a homeostasis of the alveolar ventilation if various disturbances occur.
Keywords: Dihanje; Respiration; Pljučna ventilacija; Pulmonary Ventilation; Bronchoconstriction; Bronhokonstrikcika; Functional Residual Capacity; Dihalna mehanika; Funkcionalna, rezidualna kapaciteta; Respiratory Mechanics; Računalniška simulacija; Computer Simulation; pljuča; ventilacija; modeli; fiziologija